Whole extruded linseed in the diet of dairy ewes during early lactation: effect on the fatty acid composition of milk and cheese - P. Secchiari; M. Del Viva; A. Pollicardo; G. Conte; A. Serra; M. Mele (Italian Journal of Animal Science, 2010)
In a long term supplementation trial (10 weeks), the effects of the inclusion of whole extruded linseed in the diet of dairy ewes on milk and cheese fatty acid composition were evaluated. Two groups of 24 Sarda ewes in early lactation were randomly assigned to control concentrate (800 g/d concentrate, C) or whole extruded linseed concentrate (L, 700 g/d, with 30% of extruded linseed, Omega-Lin®). Results showed that, after 2 weeks on the L diet, the milk content of unsaturated fatty acid (UFA), including rumenic acid (RA), vaccenic acid (VA) and alfa-linolenic acid (ALA) increased sharply compared to C group, reaching the highest levels after 7-8 weeks (3.06, 7.31 and 2.31 g/100 g milk fat for RA, VA and ALA, respectively). During the last 2 weeks of the experimental period, when pasture was included in the diet of both groups, the content of the above fatty acids slightly decreased in milk from L group, whereas in milk from C group increased. Nevertheless, the average content of these fatty acids in milk from L group remained significantly higher than that of milk from C group. Compared with the control, the L diet resulted in a significant reduction (-17%) in the concentration of saturated fatty acid in milk. The fatty acid content of the cheese obtained from milk of the two groups reflected the milk fatty acid composition. The inclusion of extruded linseed in the diet of dairy ewes improved the nutraceutical properties of milk and cheese, but further researches are needed in order to better understand the relationship between basal diet and lipid supplementation in dairy ewes.